THE EFFECT OF VITAMIN E AND DEXAMETASONE TO HISTOPATOLOGICAL OF WHITE MALE RATS HEART - Pratama, Ayu Prawitasari Citra; Berata, I Ketut; Samsuri, Samsuri; Merdana, I Made (Buletin Veteriner Udayana, 2018)
Dexamethasone is a widely used synthetic glucocorticoid by people. However, the use of high doses of the long term can affect the heart. The heart is the place where drugs and other toxic substances are metabolized. However, specific studies in examining the effect of dexamethasone on heart’s histopathology are rare. Vitamin E is a fat-soluble vitamin that acts as an antioxidant which can help the body to eliminate oxidative stress in cells. The aim of this study is to know the effect of vitamin E in rat’s ( Rattus norvegicus ) heart given dexamethasone. This study used 25 male rats (Rattus norvegicus), which were two-three months old and 200-300 g of weight. Rats were grouped into five treatment groups and five repeats. Rats adapted for a week, and furthermore, rats were given treatments for 14 days. In the P0 treatment group rats given only food and drink (negative control). Treatment group P1, P2, P3, and P4 were given dexamethasone 0.13 mg/kg by subcutaneous injection. Vitamin E administrated orally with the following doses: P2 (100 mg/kg), P3 (150 mg/kg), and P4 (200 mg/kg). After 14 days, then the rats were necropsied to collect the heart. Next, the heart was put into Neutral Buffered Formalin (NBF) for fixation, then stained with hematoxylin-eosin staining (HE). The observed parameters were inflammation and necrosis of the heart. The result showed administration of 200 mg/kg of vitamin E had highly significant (P<0.01) to repair of rats’ heart tissue which were given 0.13 mg/kg of dexamethasone via subcutaneous injection rather than 200 mg/kg of vitamin E. The conclusions of this study are vitamin E can against heart damage due to side effects of dexamethasone.